All Days 2011
DOI: 10.2118/142854-ms
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Well Integrity Risk: A Qualitative Model

Abstract: For successful delivery of Well Integrity, there needs to be an understanding of the risks that can cause undesirable events such as safety hazards or loss of containment. Performing a risk assessment on a well, or type of well, will help determine and rank the potential risks and provide information that allows limited resources to be applied in the most effective manner. The main objectives of performing a risk assessment include: Follow a formal process to assess risk consistently and to enable comparison b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Risk matrices are easy to implement and can be implemented even where data are limited. Therefore, they have become popular decision‐support tools in both the public and private sectors, in areas such as well‐integrity risk, drilling hazard management, climatic change responses, and so on. However, despite its simplicity and wide usage, recent research has revealed several flaws in the risk matrix.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk matrices are easy to implement and can be implemented even where data are limited. Therefore, they have become popular decision‐support tools in both the public and private sectors, in areas such as well‐integrity risk, drilling hazard management, climatic change responses, and so on. However, despite its simplicity and wide usage, recent research has revealed several flaws in the risk matrix.…”
Section: Introductionmentioning
confidence: 99%
“…The answers to the first question (a) depend on the goals of using the risk matrix. If one employs risk matrices to assist in determining the acceptance of a risk, perhaps three risk ratings are sufficient, such as “broadly acceptable,” “as low as reasonably practicable,” and “unacceptable.” However, when risk matrices are used to prioritize several risks, risk matrices should have a higher resolution to better differentiate all the risks . As a result, when we design the rating scheme of a risk matrix, the method we use should work as well as possible regardless of the various inclinations for resolution.…”
Section: Introductionmentioning
confidence: 99%